Why the Philippine Left Must Take the Parliamentary Road - Ciria-Cruz, Rene (Kasarinlan: Philippine Journal of Third World Studies; Vol 7 No 4 (1992), 2009)
Since the overthrow of the fascist dictatorship, the Philippine left's main contingent, the Communist Party of the Philippines (CPP), the force that set the pace for the country's broad progressive movement in the Marcos era has had serious difficulties. The party and its organizations - the National Democratic Front (NDF), the New People's Army (NPA), and various mass formations - have visibly lost political momentum and initiative. By all indications, the CPP is in the midst of a leadership crisis rooted in unresolved theoretical issues. The malaise reflects itself in increasing fragmentation, cadre attrition, and the undeniable erosion of considerable influence and prestige among the masses, particularly among the so-called middle sectors.